Electrochemical-thermal modelling of commercially available cylindrical lithium-ion cells for the tropical climate of India. (2021) - Shrimali, Hardik; Patel, Purvesh; Patel, Roma; Ray, Abhijit; Mukhopadhyay, Indrajit
Abstract: Lithium-ion cells are the most commonly used portable energy storage devices due to their high specific energy and energy density but have certain thermal issues that raise safety concerns. The cynosure of this work is to prepare an accurate electrochemical-thermal model of commercially available 18650 Li-ion cells of various chemistries, for tropical countries (like India). The developed model can be used for thermal analysis of diverse desired battery pack configuration and various battery cooling strategies. Newman Pseudo Two Dimensional (P2D) model is employed as it can accurately capture Li-ion migration within the cell. Nyquist plots are generated for the selected cells and Warburg constants used in the determination of Li-ion diffusion coefficients from Electrochemical Impedance Spectroscopy. This battery model was used to simulate commercial cells at discharge rates of 1C, 2C and C/2 for 3600 s, 1800 s and 7200 s, respectively. Different parameters like heat generation, temperature distribution, current densities, voltage, DOD are estimated in the model discussed here.